GROSS DOMESTIC PRODUCT: Financing & Investment Activities and State Expenditures - Fatmawati, Karina (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2022)
The growth of an economy is influenced by many factors, both micro and macro. Directly, economic and financial instruments have a close relationship to the dynamics of GDP, so they receive special attention. In its implementation, economic growth is also influenced by investment activities, banking financing, and state spending. To study this phenomenon, a quantitative method is used with the Vector Error Correction Model analysis technique. In this analysis, attempts to see which model is better in influencing economic growth with realistic data. The results of the study show that, in general estimation models, there is a possibility that economic growth is influenced by state spending, investment activities and bank financing. However, in the long-term model test, the state expenditure factor is the only variable in this study that has a positive trend towards economic growth. Because it has a greater opportunity in moving the economic sector.